Peningkatan Kualitas Lembaga Pendidikan Melalui Pendekatan Lean Six Sigma - Durrotul Masruroh (Muaddib: Jurnal Pendidikan Agama Islam, 2023)
Improving the quality of Islamic educational institutions needs to continue to be pursued by prioritizing the theory of quality analysis and its application in every managerial process. But in reality, the problems faced by Islamic educational institutions are so diverse. Starting from management problems, leadership problems, human resources, finance, and institutional problems. This study aims to examine "Improving the Quality of Education Through a Lean Six Sigma Approach" using a Qualitative Research Methodology type of case study at Nurul Jadid University in 2022. The instruments that researchers use to document data, the use of cellphones and recorders during the interview. The result of the study is to improve the quality of educational institutions at Nurul Jadid University through Lean Six Sigma, which is a stage with five steps in improving the quality of education, namely Define, Measure, Analyze, Improve, and Control. The implementation of these five stages improves the quality of educational institutions at Nurul Jadid University. its need uses the Lean Six Sigma approach to improve the quality of educational institutions which are currently experiencing a lot of declines.